Between García Lorca and Carr: translating dialect, orality, and cultural identity in Marina Carr’s adaptation, Blood Wedding (Estudios de Traducción, 2026)
This article analyzes Terrazas and Errami’s (2025) Spanish translation of Marina Carr’s Blood Wedding (2019), a reimagining of Federico García Lorca’s Bodas de sangre (1933). Carr reframes Lorca’s rural tragedy through an Irish Midlands lens, where Hiberno-English carries crucial social and performative functions. The central challenge was to preserve this dialectal, oral, and symbolic texture while ensuring legibility and stage-readiness for Spanish audiences steeped in Lorca’s canon. We adopt a strategy of parallel dialect translation, using calibrated Andalusian features, apocope, aspiration, lenition, and yeísmo, as functional equivalents that maintain rusticity, rhythm, and character markedness without caricature. The discussion addresses problems of poetic cadence, culture-specific lexis, proverbiality, and onstage musicality, and justifies oblique choices over literalism where necessary to sustain dramatic effects. We argue that theater translation operates as cultural mediation: it preserves key indices of Irishness while productively resonating with the Andalusian oral tradition, thereby enabling a new reception horizon. The result is a performable script that retains Carr’s dramaturgical pulse and reconfigures Lorca’s in a contemporary Spanish-speaking context. The translation allows audiences to re-encounter a classic tragedy from a contemporary and gender-conscious perspective. Ultimately, it underscores the need for reinterpretations that reflect evolving social values and global artistic dialogues.